Pembelian Impulsif pada Remaja Akhir Ditinjau dari Kontrol Diri - Ardian Rahman Afandi; Sri Hartati (Faculty of Psychology, Universitas Gadjah Mada, 2017)
This study aims to examine the role of self-control on impulsive buying among late adolescence. The hypothesis of this study is that self-control has a role in impulsive buying. Five hundred and nine subjects consisted of freshmen from 18 faculties and 1 vocational school participated in this study. Measuring instruments used in this study were adapted from an impulsive buying scale and a self-control scale. The results of this study can be concluded that self-control has a role in impulsive buying among late adolescence. Additional analysis indicates that there were differences in impulsive buying rates in the gender group and the amount of money that they received monthly from parents, while the difference in self-control rates was shown in the cluster group